Towards an authentic North-South NGO Partnership : a case study of the cooperation between Emmaus Helsinki and Yayasan Penghibur - Uusitalo, Sanna (2007)
The purpose of this thesis is to explore possibilities for an authentic partnership between development NGOs under the circumstances of material dependency. An authentic partnership signifies an equal, reciprocal relationship between organizations, while they are able to retain their autonomy in the cooperation. There has been extensive criticism that the realization of authentic partnerships is severely complicated by Southern NGOs’ financial dependency on Northern NGOs, resulting in organizational relationships of control and inequality. The research is a case study of the partnership between two NGOs, Emmaus Helsinki in Finland and Yayasan Penghibur in Indonesia. The aim of the research is to gain a comprehensive understanding of the cooperation, assessing its qualities as an authentic partnership. The role of trust is emphasized for the fact that trust between organizations is seen as a factor, which can make an authentic partnership possible despite significant material dependency. It is argued that trust can enhance the autonomy of each organization and thus enable an authentic partnership. This research explores the trust relations between Emmaus Helsinki and Yayasan Penghibur, the linkages between trust and the use of power, and the issues of equality and dependency between the organizations. The research was conducted by using qualitative methods. The primary data of this research consists of eight interviews conducted with representatives of each organization. The interviewing technique was semi-structured. Written documents produced by both organizations were used as secondary data for the research. According to research findings, the partnership between Emmaus Helsinki and Yayasan Penghibur is very trust-based. In the cooperation this has resulted in the significant autonomy of Yayasan Penghibur, which despite material dependency exercises great control over its operations. Equality between the organizations is further encouraged by the attitudes on equality which are prevalent in Emmaus Helsinki. Formalizing the partnership to a greater degree is suggested in order to clarify the relationship between the organizations and create more security.